Gestational Age and Cognitive Ability in Early Childhood: a Population‐based Cohort Study. Issue 4 (28th May 2013) - Poulsen, Gry; Wolke, Dieter; Kurinczuk, Jennifer J; Boyle, Elaine M; Field, David; Alfirevic, Zarko; Quigley, Maria A
Abstract: Background: Recent studies suggest that children born at late preterm (34–36 weeks gestation) and early term (37–38 weeks) may have poorer developmental outcomes than children born at full term (39–41 weeks). We examined how gestational age is related to cognitive ability in early childhood using the UK Millennium Cohort Study. Methods: Cognitive development was assessed using Bracken School Readiness Assessment at age 3 years, British Ability Scales II at ages 3, 5 and 7 years and Progress in Mathematics at age 7 years. Sample size varied according to outcome between 12 163 and 14 027. Each gestational age group was compared with the full‐term group using differences in z‐scores and risk ratios for scoring more than −1 SD below the mean. Results: Children born at <32 weeks gestation scored lower ( P  < 0.05) than the full‐term group on all scales with unadjusted z‐score differences ranging between −0.8 to −0.2 SD. In all groups, there was an increased risk ( P  < 0.05) of scoring less than −1 SD below the mean compared with the full‐term group for some of the tests: those born at < 32 weeks had a 40–140% increased risk in seven tests, those born at 32–33 weeks had a 60–80% increased risk in three tests, those born at 34–36 weeks had a 30–40% increased risk in three tests, and those born at 37–38 weeks had a 20% increased risk in two tests. Conclusions: Cognitive ability is related to the entire range of gestational age, including children born at 34–36 and 37–38 weeks gestation.